Glycerol dialkyl glycerol tetraethers (GDGT) distributions from soil to cave: Refining the speleothem paleothermometer. (October 2019) - Baker, Andy; Blyth, Alison J.; Jex, Catherine N.; Mcdonald, James A.; Woltering, Martijn; Khan, Stuart J.
Graphical abstract: Highlights: GDGTs in soil, in-cave surfaces and cave drip water analysed at two caves. GDGT distributions differ between soils, in-cave surfaces and drip waters. Global modern speleothem GDGTs distributions differ from these potential sources. TEX86 is a robust speleothem GDGT paleothermometer recording cave temperature. Improved understanding and measurement of cave temperatures is important. Abstract: The glycerol dialkyl glycerol tetraether (GDGT) paleothermometer has potential application as a speleothem paleoclimate proxy. However, the sources of GDGTs found in speleothems are poorly understood, with multiple potential sources of GDGTs from the soil to the speleothem surface. Here we analysed GDGTs in soils, soil leachates, in-cave surfaces and cave drip waters at two Australian montane caves. We observed significantly different GDGT distributions between soils, soil leachates, in-cave surfaces and drip waters and significant spatial differences in in-cave GDGT distributions. Comparison with published modern in-cave and karst groundwater GDGT datasets from Australia, Europe and China shows that speleothem GDGT distributions are different from those of all potential sources. We hypothesise that speleothem surfaces have a calcifying, alkaline, oxic, wet, carbon-available, environment that supports a microbial community that is different from other possible karst GDGT sources. We propose that the presence of GDGTs related to anoxic or methanogenic conditions, and observed in cave drip water and on in-cave surfaces, can be used to identify GDGTs from these sources. We confirm that TEX86 based paleothermometers are robust speleothem GDGT paleothermometers, whose calibration can be further refined through improved understanding and measurement of cave temperatures.